Kekerasan terhadap Perempuan dalam Film Indonesia (Analisis Isi Kuantitatif dalam Film Indonesia dengan Latar 1998-2021) - Arselly Dwi Cahyani; Monika Pretty Aprilia (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
Film as a mass media can describe and be a portrait of the reality that occurs in society. Several Indonesian films that highlight the reality of violence against women are “Penyalin Cahaya”, “27 Steps of May”, “Posesif”, “Raksasa dari Jogja”, “Marlina si Pembunuh dalam Empat Babak”, “Jamila dan Sang Presiden”, and “7 Hati 7 Cinta 7 Wanita”. This study aims to determine the forms of violence against women in Indonesian films with a 1998-2021 background. As well as knowing how often the occurrence of scenes of violence against women in these films is. In addition, the researcher wanted to know how the characters in the film used coping strategies to overcome the violence they experienced. This research was conducted using quantitative content analysis method. The results of this study indicate that the violence that appears in the form of physical violence (24%), psychological violence (31%), and sexual violence (45%). It was also found that the women in the films tended to face the violence they experienced with emotion focused coping. Keyword:  Indonesian film, content analysis, violence against women, coping strategy